Correction to: Seeking care in the context of social health insurance in Kenya and Ghana - Lauren Suchman; Catherine Verde Hashim; Joseph Adu; Rita Mwachandi (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.